Heritability estimation of milk production of cows of different origin and breed in Karacabey State Farm - Dogan, I; Ertugrul, O (Tubitak Scientific & Technological Research Council Turkey, 1999)
The objective of this study was to estimate heritability (h(2)), a useful criterion, in the improvement studies which would De conducted to improve milk productivity in the Karacabey State Farm. A total of 760 cows, of which milk yield records were used in the study in different lactation period, consisted of 111 American Browns, 142 American Holsteins, 87 German Browns, 130 Swiss Browns, 83 Holland Holsteins and 207 Karacabey Browns. Milk yields were corrected according to the 2x305ME standardisation procedure, Furthermore, coefficients of relationship were calculated separately for Brown and Holstein cows using the pedigree cards of the animals whose milk yield records were utilised in the study. The heritability coefficients for milk yield according to the origin of the animals were estimated by using the Half Sib-Correlation Method. Heritability coefficients: Utilising 305ME corrected milk yields of all daughters of each sire secured, Considering 305ME corrected milk yields of at least 5 daughters of each sire, Using actual milk yields of at least 5 daughters of each sire, were estimated for three different situations. Again, heritability coefficients were calculated one by one considering the coefficients of relationship obtained from the study and those from the method itself. The animals were grouped according to origin and the heritability coefficient for each origin was estimated one by one, but the results were not found to be satisfactory. The most suitable result was reached when the breed rather than the origin was considered and in the cases where new relativity degrees obtained were used for sires having at least five daughters. Accordingly, estimated Heritability coefficient for milk yield were as follows: for Brown Swiss :0.3050 +/- 0.1182 for Holstein :0.2926 +/- 0.2562.
Karacabey Tarim İşletmesindeki Farkli Irk ve Kökenlere Sahip İneklerin Süt Verimlerinin Kalitim Derecelerinin Tahmini
Keywords: cattle; brown Swiss; Holstein; milk yield; heritability